0506 Clinical efficacy of intravenous ferric carboxymaltose for restless legs symptoms and low serum ferritin in children with autism spectrum disorder. (25th May 2022) - DelRosso, Lourdes; Cho, Yeilim; Ferri, Raffaele; Krell, Melissa; Reuter-Yuill, Lilith; Mogavero, Maria; Picchietti, Daniel
Abstract: Introduction: Restless legs syndrome (RLS) may be underdiagnosed in children with autism spectrum disorder (ASD) due to difficulty expressing the symptoms in their own words. In addition, administration of oral iron may be particularly difficult in ASD children. Methods: Retrospective case series of children with ASD, restless legs (RL) symptoms, and serum ferritin <30 μg/L treated with intravenous (IV) ferric carboxymaltose (FCM). Patients received a single dose of IV FCM, 15 mg/kg if weighting <50 kg or 750 mg if weighting >50 kg. Data collected included presenting symptoms, serum ferritin, iron profile, and Clinical Global Impression Scale (CGI-Severity pre-infusion and CGI-Improvement post-infusion). Results: Nineteen subjects, 4-11 years old (12 male, median age 6, interquartile range (IQR) were included. Thirteen children took melatonin, median dose 3 mg (IQR 1-6). Full RLS diagnostic criteria were identified in 6 verbal children (31.6%). RL symptoms in the 13 other children occurred at night and began or worsened during periods of rest or inactivity and included: need for a parent to rub or massage legs (5), fidgeting (2), wiggling (2), kicking (2), pacing (1), and discomfort (1), but improvement of symptoms with movement was difficult to determine. Baseline median values were ferritin 10 µg/L (IQR 10-16), iron 66.5 μg/dL (IQR 57-96), TIBC 382 μg/dL (IQR 360-411) and transferrin 19 mg/dL (IQR 14-28). Median CGI-S was 4 (moderate symptoms) (IQR 3-4). After IV FCM all measures improved and were statistically significant at the Wilcoxon test for paired datasets. Median ferritin was 68 µg/L (IQR 62.5-109, p<0.00045). The median CGI-I was 1 (very much improved) (IQR 1-2). All children meeting full RLS criteria improved. Three children in the RL symptom group did not improve. Children meeting the full RLS criteria had lower baseline ferritin levels than those with a suspected diagnosis (9 µg/L, IQR 9-10 vs. 13 µg/L, IQR 10-16, Mann-Whitney test p<0.045). Conclusion: The majority of children (84.2%) with ASD and RL symptoms had clinical improvement after IV FCM. All serum iron parameters improved significantly after a single IV infusion. Support (If Any): None